2015
DOI: 10.1186/s13643-015-0142-z
|View full text |Cite
|
Sign up to set email alerts
|

Nebulised dornase alfa versus placebo or hypertonic saline in adult critically ill patients: a systematic review of randomised clinical trials with meta-analysis and trial sequential analysis

Abstract: BackgroundNebulised dornase alfa is used off-label in critically ill patients. We aimed to assess the benefits and harms of nebulised dornase alfa versus placebo, no prophylaxis, or hypertonic saline on patient-important outcome measures in adult critically ill patients.MethodsWe performed a systematic review with meta-analysis and trial sequential analysis (TSA) using the Cochrane Collaboration methodology. Eligible trials were randomised clinical trials comparing nebulised dornase alfa with placebo, no proph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Deoxyribonuclease (DNase) digests polymerized DNA; hence, it reduces mucus viscosity and promotes mucus clearance in the CF airways. Therefore, the use of aerosolized recombinant human DNase I (dornase alfa) is an attractive approach to alleviate DNA-related mucus viscosity in patients with CF [197]. One caveat; however, is the inhibition of the enzyme by globular actin.…”
Section: Clearing Neutrophil Extracellular Traps (Nets)—dnases Andmentioning
confidence: 99%
“…Deoxyribonuclease (DNase) digests polymerized DNA; hence, it reduces mucus viscosity and promotes mucus clearance in the CF airways. Therefore, the use of aerosolized recombinant human DNase I (dornase alfa) is an attractive approach to alleviate DNA-related mucus viscosity in patients with CF [197]. One caveat; however, is the inhibition of the enzyme by globular actin.…”
Section: Clearing Neutrophil Extracellular Traps (Nets)—dnases Andmentioning
confidence: 99%
“…A systematic review with meta-analysis found only 2 trials comparing nebulized dornase alfa with placebo, no therapy, or hypertonic saline. 168 The evidence was of low quality and did not report any benefit or harm from use of nebulized dornase alfa in critically ill patients. Mucoactive agents may have a role in preventing lung collapse and hypoxemia in ventilated patients with thick inspissated secretions who are refractory to other forms of treatment.…”
Section: Avoid Inappropriate Therapiesmentioning
confidence: 94%
“…14,15,18 Nevertheless, the most recent meta-analysis evaluating the therapeutic and prophylactic nebulization of mucoactive agents in adult critically ill patients found very low quantity and quality of evidence to support their use. 14 Little evidence exists of their prophylactic use in the pediatric critical care setting to decrease the duration of mechanically ventilation, and no prospective blinded studies in children undergoing mechanical ventilation have been reported.…”
Section: See the Original Study On Page 586mentioning
confidence: 99%
“…Despite some obvious limitations of the study by Shein et al 15 , their results are consistent with a few trials where nebulized hypertonic saline did not significantly improve any of the clinical outcomes measured. 14,18,19 The evidence supporting the prophylactic use of nebulized hypertonic saline for patients undergoing mechanical ventilation as a mucoactive agent and its impact on clinical outcomes is lacking. This study invites clinicians to take a closer look at the potential prophylactic role of mucoactive agents to improve mucociliary clearance and possibly impact important clinical outcomes, such as ventilator length of stay.…”
Section: See the Original Study On Page 586mentioning
confidence: 99%